ASUHAN KEBIDANAN PADA IBU HAMIL DENGAN EMESIS GRAVIDARUM - Ika Putri Damayanti (Ensiklopedia of Journal, 2020)
Emesis gravidarum is discomfort in pregnant women with nausea and vomiting that occurs in the first trimester of pregnancy. Nausea usually occurs in the morning, but can also occur at any time and night. Factors that cause emesis gravidarum include hormonal changes in the body during pregnancy, namely increased estrogen and HCG (human chorionic gonadotrophin). HCG is a hormone produced by the placenta during pregnancy in the body of pregnant women, in addition to psychological factors such as anxiety, guilt, including support given by the husband to the mother, social environmental factors, cultural and economic conditions. Emesis gravidarum is a natural symptom or is often found in trimester pregnancy I. This study aims to determine the success of midwifery care given to pregnant women Trimester I with emesis gravidarum they experienced. Care was provided in 2 second visits using the SOAP documentation approach. The case was taken by visiting Pratama Karya Bakti Clinic located on Jl. Sail, Kelurahan Rejosari, Tenayan Raya District, Pekanbaru City. Midwifery care for first trimester pregnant women with nausea and vomiting by providing health education and vitamin B6 therapy. From midwifery care in trimester I pregnant women with emesis gravidarum for 2 times the mother's condition improves, namely nausea and vomiting experienced can be reduced.